Regulatory roles and therapeutic potential of microRNA in sarcoma. (January 2016) - Lim, Hui Jun; Yang, Jia-Lin
Abstract: Purpose: MicroRNAs (miRNAs) are single-stranded noncoding RNAs involved in various biological processes, including cell differentiation and development. They play multiple key roles as tumour suppressors, oncogenes or both in particular cases. This review aims to summarise current findings of the expression of miRNAs and their role in clinical oncology. Current knowledge regarding the involvement of miRNAs in different sarcoma subtypes will be assessed, in conjunction with their potential application as therapeutic targets. Methods: Relevant articles in scientific databases were identified using a combination of search terms, including "microRNA, " "deregulation, " "sarcoma, " and "targeted therapy". These databases included Medline, Embase, Cochrane Review, Pubmed and Scopus. Results: Aberrant miRNA expression patterns have been identified in a range of sarcoma subtypes, and differences in miRNA expression profiles between malignant cells and their normal counterparts suggests that miRNAs play key roles in sarcoma development. The identification of unique miRNA patterns in individual tumour types could possibly be used as a diagnostic tool in sarcoma. Moreover, identification of these miRNAs provides novel targets for the development of therapeutic strategies in distinct sarcoma subtypes. Conclusion: miRNAs hold significant potential as diagnostic biomarkers, as well as therapeutic targets in sarcoma. Possible future clinical applications include the use of miRNA pathways as therapeutic targets or miRNA expression profiling as a means of patient selection. The involvement miRNAs will undoubtedly contribute to the advancement of future targeted therapeutic interventions in sarcoma, and further establishment of appropriate delivery systems is vital for their use in clinical settings.